Green recovery: perspectives for the return of the economy after the pandemic caused by COVID-19 from the green job program (Research, Society and Development, 2022)
The presente work aims to analyze the green job program, established by the ILO in 2008, as na instrument for economic recovery in a post-pandemic scenario caused by COVID-19 and its variants. The program in question touches on one of the main dilemmas of contemporaneity when it seeks to reconcile economic interests and environmental sustainability, according to the precepts of the Federal Constitution of 1988. This is because it is an instrument that recognizes free enterprise as one of the pillars of the economic order, as well as the valorization of human work and the preservation of the environment. The research has a qualitative nature, based on the understanding of social phenomena, it has an exploratory character and uses the hypothetical-deductive methodology, with analysis of documental and bibliographic research to address the theme and analyze the expansion of the green job program for creatin of new jobs and promoting green recovery.